ADAPTATION OF THE EDUCATIONAL PROGRAM FOR FINANCIAL CALCULATIONS ACCORDING TO THE ACTUAL ECONOMIC STATE - Ekaterina P. Mochalina (Plekhanov Russian University of Economics, 2017)
This paper presents an innovative approach to teaching the discipline ‘Financial calculations‘, which based on a dynamic block of case studies generated by information received online from the stock market. Method is described by the case study ‘Evaluation of financial assets, the expected return and volatility‘. Details shows how work in practice well-known classic models and how exactly the adjustment of the results is made. Adequacy of conclusions obtained with this approach is easily testable (a system with an open content), that is, from the point of view of the authors, an additional advantage of the proposed model of learning.